How solvent determines the molecular reactive conformation and the selectivity: Solvation spheres and energy - Hernández-Lima, Joseelyne; Ramírez-Gualito, Karla; Quiroz-García, Beatriz; Silva-Portillo, Ana Luisa; Carrillo-Nava, Ernesto; Cortés-Guzmán, Fernando (Frontiers in Chemistry, 2022)
In solution, the solvent determines the molecular conformation and the chemical reaction viability and selectivity. When solvent-solute and solvent-solvent interactions present similar strengths, explicit salvation is the best way to describe a system. The problem to solve is how big the explicit shell should be. In this paper, we want to answer one of the fundamental questions in the implementation of explicit solvation, exactly how many solvent molecules should be added and where they should be placed. Here we determine the first solvent sphere around a molecule and describe how it controls the conformation and selectivity of a selected reaction. NMR experiments were carried out to identify the number of solvent molecules around the solute that constitutes the first solvent sphere, and the interaction between this solvent sphere and the solute was detected using DFT and QTAIM calculations. A new approach to the solvation energy is presented. Finally, we established the role of solvent molecules in the conformation of the solute and in the transition states that produce the two possible products of the reaction.